2003
DOI: 10.1076/ceyr.27.5.301.17227
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase in the retina in diabetes

Abstract: The present data suggests that the HO system is up-regulated in short term diabetes leading to HO and NO interactions which may modulate vascular function in the retina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 51 publications
3
26
1
Order By: Relevance
“…Haemoxygenase-1 levels in diabetic retina Consistent with previous reports [25,26], this study identified differences in the pattern of retinal levels of the oxidative stress marker haemoxygenase-1 when diabetic retinas were compared with controls (p < 0.001). As shown in Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Haemoxygenase-1 levels in diabetic retina Consistent with previous reports [25,26], this study identified differences in the pattern of retinal levels of the oxidative stress marker haemoxygenase-1 when diabetic retinas were compared with controls (p < 0.001). As shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…Pyridoxamine also prevents ALE formation in diabetic and obese rats [36,37] through cleavage of alpha-dicarbonyl intermediates in glycoxidation and lipoxidation reactions [38]. It also effectively reduced upregulation of retinal haemoxygenase-1, which is significant as this enzyme has been previously used as a reliable marker of oxidative stress in diabetic retinopathy [25,26]. It is known that AGE/ALE adducts are linked to generation of reactive oxygen species in the central nervous system [39].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that HO-1 is upregulated in monocytes from patients with type 2 diabetes (Avogaro et al, 2003). Experimentally, diabetes leads to upregulation of HO-1 in retinal vessels (Cukiernik et al, 2003); however, data from other groups indicate that HO activity is decreased in aortas from diabetic rats compared with control (Quan et al, 2004). Abraham et al found that high glucose inhibited HO activity and decreased HO-1 protein in endothelial cells .…”
Section: Discussionmentioning
confidence: 97%
“…An overwhelming body of evidence indicates that the heme-HO system is intrinsically involved in the regulation of many physiological and pathophysiological processes, including diabetes (27,28). Hyperglycemia may also enhance retinal ROS production causing cell damage and death.…”
Section: Discussionmentioning
confidence: 99%